399 COMPARISON OF COGNITIVE FUNCTION AND QUALITY OF LIFE IN WOMEN WITH HYPOPITUITARISM: ROLE OF ANDROGENS. (1st January 2005) - Zuckerbraun, E.; Garcia, M.; Tran, B.; Friedman, Bhasin S. T.C.
Abstract : Objective: The role of testosterone in cognitive and psychological function in women remains poorly understood. Women with hypopituitarism have severely diminished ovarian and adrenal androgen production and thus represent an excellent model to study the consequences of androgen deficiency. We hypothesized that women with hypopituitarism would exhibit altered psychological function and decreased quality of life as a result of androgen deficiency. Method: Total testosterone, cognitive function and quality of life questionnaires (POMS, NHP Questionnaire, Fatigue Impact Scale, SCL-90-R) were obtained from 15 women with documented hypopituitarism (median age 37.5±7.1, BMI 28.1±5.2) and 9 aged-matched healthy volunteers (median age 26±9.2, BMI 25.6±4.2) in an IRB-approved study. Results: Total testosterone levels were markedly diminished among women with hypopituitarism (4.7±3.9 ng/dL) compared to normal volunteers (25.5±2.7 ng/dL, p≤0.0005). All cognitive function and quality of life questionnaires (POMS, p≤0.001; NHP Questionnaire, p≤0.005; Fatigue Impact Scale, p≤0.005; SCL-90-R, p≤0.05) showed marked differences in psychological function and fatigue in the patients with documented hypopituitarism compared to aged-matched healthy volunteers controls. Conclusion: Based on this data, we postulate that testosterone deficiency in women with hypopituitarism leads to impairment of cognitive function and a marked decrease in their quality of life. These data provide compelling rationale for placebo-controlled, randomized trials of testosterone replacement in women with hypopituitarism.